1998
DOI: 10.1097/00000658-199802000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Living Related Liver Transplantation in Adults

Abstract: ObjectiveTo evaluate the outcome of living related liver transplantation (LRLT) in adult patients and to assess graft size disparity and graft regeneration. Summary Background DataAlthough LRLT has been accepted as an optional life-saving procedure for pediatric patients with end-stage liver disease, the feasibility of LRLT for adult patients has not been reported with reference to a clinical series. MethodsAdult-to-adult LRLT was performed using whole left lobar grafts in 13 patients (5 with primary biliary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
242
0
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 392 publications
(248 citation statements)
references
References 15 publications
0
242
0
6
Order By: Relevance
“…Efforts have been made to use LRLT for critical cases of FHF, 9 and for adult patients in whom small-for-size grafts have been used. 22 In our series of 106 LRLTs, the reasons for transplantation were biliary atresia in 52, FHF or SFHF in 14, primary biliary cirrhosis in 12, familial amyloid polyneuropathy in 11, citrullinemia in 5, Alagille' s syndrome in 4, and others in 8 patients. Thirtyseven LRLTs (35%) were performed on adult patients.…”
Section: Discussionmentioning
confidence: 76%
“…Efforts have been made to use LRLT for critical cases of FHF, 9 and for adult patients in whom small-for-size grafts have been used. 22 In our series of 106 LRLTs, the reasons for transplantation were biliary atresia in 52, FHF or SFHF in 14, primary biliary cirrhosis in 12, familial amyloid polyneuropathy in 11, citrullinemia in 5, Alagille' s syndrome in 4, and others in 8 patients. Thirtyseven LRLTs (35%) were performed on adult patients.…”
Section: Discussionmentioning
confidence: 76%
“…In clinical ALT, the graft can be reduced to a right liver (approximately 65 YO of the whole liver volume), a left liver (35 YO) or a left lobe (20%) [2,4,12]. In ALT for FHF, the necessity of quick restoration of liver function and reversal of cerebral oedema argues for the use of the right liver [2,4, 141.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are two standards worldwide: one is ratio of grafts to recipients' weight (GRWR) and the other is ratio of grafts volume to recipients' standard liver volume (GV/SLV). It is generally thought that the former should be more than 0.8% (Fan et al, 2000), and the latter should be more than 40% (Kawasaki et al, 1998). According to the Fan et al (2000) criteria, the volume of remnant liver should exceed 30%, while Lee et al (2001b) believes that the volume of remnant liver should exceed 35% (Kawasaki et al, 1998).…”
Section: What Guidelines Must Be Observed When Performing Dual Liver mentioning
confidence: 99%
“…It is generally thought that the former should be more than 0.8% (Fan et al, 2000), and the latter should be more than 40% (Kawasaki et al, 1998). According to the Fan et al (2000) criteria, the volume of remnant liver should exceed 30%, while Lee et al (2001b) believes that the volume of remnant liver should exceed 35% (Kawasaki et al, 1998). Previous study has shown, in Table 2 in the first seven cases, average GRWR and GV/SLV to be 1.06% and 58.1%, respectively, with good results, but from Cases 8 to 25, GV/SLV ranges from 46.6% to 78.9% with three patients dying (Lee et al, 2001b).…”
Section: What Guidelines Must Be Observed When Performing Dual Liver mentioning
confidence: 99%
See 1 more Smart Citation